Persepsi Masyarakat terhadap Kewajiban Ganda Membayar Zakat dan Pajak Studi Kasus Kota Samarinda (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
The aim of this study is to find out how the public perception of the double obligation to pay zakat and taxes in which Indonesia is a Muslim majority with a large potential of zakat. The method used in this study is qualitative descriptive research method. the Data collection techniques use observation, interview and documentation. Interviewees in this study were 10 people. The conclusion of this study indicates that the people are more obedient to pay taxes because of the strict sanction from the government. While the zakat, people already know the obligation and they are obedient to implement it but the zakat in question is zakat fitrah only, people know less about other obligations of zakat mall. Therefore, there is a need for serious government involvement to engage and socialize to the society about the obligation of the society to pay zakat.